Elevate The Employee Performance: Interplay of Job Satisfaction as Moderating on Transformational Leadership Style and Work Environment - Zulher; Suarni Norawati; Fadlan Effendi; Citrawati Jatiningrum (Jurnal Dinamika Manajemen, 2025)
This study meticulously examines the moderating effect of job satisfaction on the relationship between transformational leadership, work environment, and employee performance in civil service police units members of Kampar Regency. The research method employs the SEM-PLS approach to provide better triangulation and elaboration of cases. Data is collected through surveys and follow-up interviews with civil service police officers in Kampar Regency as respondents. The findings reveal that transformational leadership style has a significant positive effect on employee performance, while the work environment has no significant effect. Transformational leadership style significantly influences performance through job satisfaction as a mediator. However, the work environment has no significant effect on performance through job satisfaction. These results highlight that leadership style and job satisfaction undeniably influence employee performance, but their effectiveness depends on various situational and contextual factors in civil service police units as public service agencies.